DEI in Japanese Higher Education: Visible Progress, but a Long Journey Ahead - Chen , Lilan; Wang, Lizhou (International Higher Education, 2025)
This study examines Diversity, Equity, and Inclusion (DEI) implementation in Japanese higher education. An analysis of governmental policies, initiatives, university DEI declarations, and DEI center operations shows that, while DEI is promoted in response to demographic shifts, globalization, and the social inclusion agenda, implementation relies heavily on project-based funding, numerical targets, and symbolic structures. This article outlines both the progress that has been achieved and the need for expanded diversity dimensions to address structural inequities.